Identification of RAPD‐SCAR marker linked to white spot syndrome virus resistance in populations of giant black tiger shrimp, Penaeus monodon Fabricius. Issue 5 (16th August 2013) - Dutta, S; Biswas, S; Mukherjee, K; Chakrabarty, U; Mallik, A; Mandal, N
Abstract White spot disease (WSD) caused by white spot syndrome virus (WSSV) creates severe epizootics in shrimp aquaculture industry worldwide. Despite several efforts, no such permanent remedy was yet developed. Selective breeding using DNA markers would be a cost‐effective strategy for long‐term solution of this problem. In the present investigation, out of 30 random primers, only one primer produced a statistically significant (P < 0.01) randomly amplified polymorphic DNA (RAPD) marker of 502 bp, which provided a good discrimination between disease resistant and disease susceptible populations of Penaeus monodon from three geographical locations along the East coast of India. Because RAPD markers are dominant, a sequence characterized amplified region (SCAR) marker was developed by cloning and sequencing of 502 bp RAPD fragment, which generates a single 457 bp DNA fragment after PCR amplification only in the disease resistant shrimps. Challenge experiment was also conducted to validate this 457 bp SCAR marker, and the results suggested that the WSSV loads were 2.25 × 103 fold higher in disease susceptible than that in disease resistant shrimps using real‐time PCR. Therefore, this 457 bp DNA SCAR marker will be very valuable towards the development of disease‐free shrimp aquaculture industry.